Effects of burned and unburned sugarcane harvesting systems on soil CO2 emission and soil physical, chemical, and microbiological attributes - Moitinho, Mara Regina; Ferraudo, Antonio Sergio [UNESP]; Panosso, Alan Rodrigo [UNESP]; Bicalho, Elton da Silva [UNESP]; Teixeira, Daniel De Bortoli; Barbosa, Marcelo de Andrade [UNESP]; Tsai, Siu Mui; Borges, Beatriz Maria Ferrari; Cannavan, Fabiana de Souza; Souza, Jackson Antônio Marcondes de [UNESP]; La Scala, Newton [UNESP] (Elsevier, 2021)
The mechanized sugarcane harvesting system has been replacing the old manual harvesting system with the burning of the sugarcane field. The purpose of the conversion of these systems is to obtain benefits related to the improvement of soil and environmental quality, minimizing the effects of greenhouse gas (GHG) emissions, especially carbon dioxide (CO2). In this context, this study aimed to investigate the effect of burned and unburned sugarcane harvesting systems on soil CO2 emission and soil chemical, physical, and microbiological attributes. Two adjacent areas were used in this study: an unburned sugarcane area, with an eight-year history without burning the sugarcane field and high amounts of crop residues (mean of 13 t ha−1), and a burned sugarcane area, with manual harvesting after burning the sugarcane field and without crop residues on the soil surface. The soil of both areas is classified as an Oxisol. Soil CO2 emission, soil temperature, and soil moisture were assessed from 20 randomly sampling points placed in each area. Soil samples were collected at the end of the soil CO2 emission, soil temperature, and soil moisture assessments from each point at a depth of 0–0.20 m to determine soil physical, chemical, and microbiological attributes. Soil CO2 emission was, on average, 37% higher in the burned sugarcane area (2.63 µmol m−2 s−1) compared to the unburned sugarcane area (1.92 µmol m−2 s−1). Soil moisture was higher in the unburned sugarcane area (25.30%) than in the burned sugarcane area (16.02%). An opposite effect was observed for soil temperature, which presented values 2.5 °C higher in the burned sugarcane area (21.5 °C) compared to the unburned sugarcane area (19.1 °C). Soil carbon decay constant k indicated that carbon was decomposed faster in the burned sugarcane area (0.00070 days−1) than in the unburned sugarcane area (0.00046 days−1). Thus, soil carbon half-life was longer in the unburned sugarcane area (1,572.82 days) compared to the burned sugarcane area (1,033.95 days), i.e., carbon permanence time in the unburned sugarcane area was 52% higher than in the burned sugarcane area. Soil temperature, soil moisture, air-filled pore space, P, the sum of bases (Ca2+ + K+ + Mg2+), soil bulk density, soil carbon stock, soil C/N ratio, and the abundance of functional gene nifH are the most representative soil attributes that allows characterizing the CO2 emission process in soils managed with sugarcane under unburned and burned harvesting systems. Therefore, the study of these attributes should be taken into account when assessing the variability of CO2 emissions in agricultural soils. In conservationist terms, the unburned sugarcane system presents a higher potential for stabilizing soil carbon and reducing the contribution of agriculture to greenhouse gas emissions, especially CO2, when compared to the burned sugarcane system.
Keywords: Enzymatic activity; quantitative real-time PCR; Soil respiration; Straw; Sugarcane management